Bernese Periacetabular Osteotomy in a Young Adult with an Ipsilateral Renal Transplant: A Case Report. Issue 1 (27th January 2016) - Collado, Diego; Sallent, Andrea; Seijas, Roberto; Aguirre-Canyadell, Marius; Ganz, Reinhold
Abstract : Case: An eighteen-year-old woman was referred to our center because of left groin pain and was diagnosed with acetabular dysplasia. The proposed treatment was a Bernese periacetabular osteotomy (PAO). The patient had undergone two renal transplants due to polycystic kidney disease; the current, functional kidney was at the lateral inguinal fossa on the left side. The patient was on chronic immunosuppressants and antihypertensive therapy. Conclusion: The present case shows that PAO can be a safe procedure with good outcomes even in patients who have undergone renal transplantation.